Les élites de l’ancien régime libyen : reconfigurations politiques en contexte transnational - Soraya Rahem (L’Année du Maghreb)
Following the collapse of the Jamahiriya, former Libyan regime elites suffered a political downgrading and went into exile, notably to Egypt and neighboring Tunisia. The political upheavals brought about by the 2011 Arab revolts, revolutions both in Libya and in neighboring countries and the emergence of new political actors make it necessary to rearrange their situation in a transnational context. Heirs to the political ideology developed by Muammar Gaddafi, the regime's elders are trying to reorganize themselves politically from abroad in order to reposition themselves in a post-revolutionary context. Although they collectively denounce the events that led to the fall of Muammar Gaddafi, these actors do not represent a unified political force. An analysis of their political reorganization thus highlights the heterogeneity of the "green movement", divided into several currents. Gradually, the geopolitical transformations brought about by the arrival in power of a new presidency in Egypt in 2014 and by the mobilization of international actors for the resolution of the conflict from Tunisia are allowing the exiled elites to make their voices heard. Also, in the face of the evolving civil war in Libya, former regime elites are managing to redeploy themselves politically through transnational coalitions, by instrumentalizing political instability and the Islamist threat. They are thus able to mobilize their networks to influence the conflict from a distance and shape a political environment more favorable to their return to Libya. This article analyses the reconfiguration of the political elites of the former Libyan regime and highlights the way in which the transnational space may have constituted a political opportunity that allowed them to redeploy to the national political spheres.